Liberating and Diversifying Theological Education: A Subversive or Empowering Aspiration? - Yong, Amos (Cross currents, 2019)
The article focuses on consequences of the pervasive white, middle-class assumptions of dominant forms of theological education embodied in most theological schools. It mentions national issues related to police brutality and race relations and issues regarding social justice and racial reconciliation from my Asian American evangelical location. It also mentions faith-rooted organizing, gathering people for social change shaped by the deepest wells of their faith traditions.